2019
DOI: 10.1016/j.gee.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanism of hydrogen activation by frustrated Lewis pairs

Abstract: Typically, a Lewis acid and a base react with each other and form classic acid−base adducts. The neutralization reaction is however prevented by the introduction of bulky substitutes and this interesting finding leads to a new concept called "frustrated Lewis pairs, FLPs". Since both reactivities of Lewis acids and bases are remained in the same systems, FLPs have been shown many important applications. One of them is hydrogen activation, which showed for the first time the use of a non−metal catalyst for that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 77 publications
(82 reference statements)
1
32
0
Order By: Relevance
“…Theoretical studies revealed that the reactivity of FLPs is strongly determined by the geometric parameters of Lewis acid (LA) and Lewis base (LB) complexes [17–18] . Taken the H 2 activation as an example, previous density functional theory (DFT) calculations showed that the suitable distances between the acid and base centers are from 3 Å to 5 Å [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies revealed that the reactivity of FLPs is strongly determined by the geometric parameters of Lewis acid (LA) and Lewis base (LB) complexes [17–18] . Taken the H 2 activation as an example, previous density functional theory (DFT) calculations showed that the suitable distances between the acid and base centers are from 3 Å to 5 Å [19] .…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that at larger distance of the H 2 from the Lewis pair centers the electrostatic field of the LA‐LB polarizes H 2 . When the H 2 molecule is closer to the LA‐LB centers, a charge transfer form H − to LA and from LB to H + occurs [50,51] …”
Section: Resultsmentioning
confidence: 99%
“…When the H 2 molecule is closer to the LA-LB centers, a charge transfer form H À to LA and from LB to H + occurs. [50,51] To analyze the effect of substitutions on the interactions between the H À •••H + and the LA-LB fragments, in Table 4 we have shown the EDA results for compounds 1 to 4. As reported in Table 4, in case of carbon LAs, going from molecule 1 to 4 the ΔE � int becomes weaker.…”
Section: Interactions Between H 2 and La-lb At The Transition Statementioning
confidence: 99%
“…Our experimental/computational investigations regarding the heterolytic splitting of dihydrogen mediated by these pairs led us to propose a genuine bimetallic FLP-type pathway 7 analogous to the models assumed for main-group counterparts. 8 Moreover, we could analyze the strong influence that Au···Pt interactions have on the activation capacity of the bimetallic pairs, as well as the solution dynamic equilibria between the metal-only Lewis pairs and the individual monometallic fragments. This is a particularly important aspect in the field of FLPs that has been widely investigated for metal-free systems, where the term “thermally induced FLPs” 9 was coined to refer those pairs in which the Lewis adduct is the resting state.…”
Section: Introductionmentioning
confidence: 99%